PEMBERDAYAAN MASYARAKAT PETANI KOPI DALAM UPAYA MENINGKATKAN KUANTITAS KOMODITAS KOPI GUNUNG KELIR - Wilis Malasari; Eva Banowati; Hariyanto Hariyanto (Geo-Image, 2017)
This study aims to determine the role of community empowerment programs in community development as well as mechanism made gapoktan in improving the knowledge of its members and effort to increase coffee plants in the Jambu Distric Jambu Semarang regency. The method of this research is qualitative analysis and doing the test of validity and data using source triangulation. The author uses interviews and observations to obtain preliminary data in the field. Then interview information, then checked with observation, documentation, and questionnaire. Then in obtaining the same data until saturated, with questions asked researchers to various informants. Community empowerment in distric Jambu is conducted throught training and counseling held by the local goverment. Throught these efforts many farmers experience post-harvest improvement after applying the knowledge that can be from training and counseling if the farmer is active in farmer groups. The influence of farmer grop’s role in helping farmers to develop coffe cultivation business has reached 50%.